The CEFR Impact on English Language Educators teaching Engineering Programmes in a Private University in Malaysia - Abd Rahman, Ahmad Zufrie; Chong, Seng Tong; Kaman, Zeittey Karmilla; Leon, Carol Elizabeth (Journal of Techno-Social, 2021)
This paper presents some preliminary findings of a multi-dimensional and interdisciplinary research. It explores the experience of language educators on the newly implemented policy by the Ministry of Education, Malaysia. The implementation of the Common European Framework of Reference for Languages (CEFR) is a policy that develops through a whole continuum: from primary schools to universities. The paper fills the gap in terms of impact studies of the CEFR especially on engineering programmes where the desired CEFR levels are higher. This implementation affects language educators at university in various domains such as the required CEFR levels for language educators, teaching materials and support systems. The methodological framework used in this study is phenomenological study. It aims to explore the experience of the language educators. Interviews were conducted on three language educators teaching engineering programmes at a private university. Snowballing technique was used in identifying the research interviewees. Data gathered were analysed using Atlas.Ti, a qualitative analysis software. Preliminary result indicates that language educators were positive and welcome enthusiastically the change. However, challenges were immense and critical. This paper concludes that the implementation of the CEFR is a wise move for Malaysian students towards a higher level of proficiency in English.